Properties of resin impregnated oil palm wood (Elaeis Guineensis Jack) - Bakar, Edi Suhaimi; Md. Tahir, Paridah; Sahri, Mohd Hamami; Mohd Noor, M. S.; Zulkifli, F. F. (Universiti Putra Malaysia Press, 2013)
Oil palm wood (OPW) was treated with medium-molecular weight PF resin (mmw-PF) through a modified impregnation-compression method. The method consists of four steps, namely, drying, impregnation, heating, and hot pressing densification. The objective of the study was to optimize the impregnation variables. The overall density of the OPW increased, whereas the density gradient between the two OPW structural elements (namely, parenchyma tissues and vascular bundles) decreased. The weight percent gain (WPG) significantly increased even with a very short impregnation period (i.e. 1 hour). Young`s Modulus of the compression parallel to the grain increased by 15 times (from 170 to 2600 MPa) and the shear strength increased by 7 times (from 1.9 to 13 MPa). The strength of the samples was increased exponentially against density increment. The treatment also made the two OPW structural elements to be strongly bonded that helped in enhancing the durability and machining characteristics of the material.